The Effect of Using Card Sort Toward Students’ Vocabulary Mastery at Eight Grade of SMPN 7 Bukittinggi in the Academic Year 2017/2018 - Khabib Muafi; Veni Roza (English Language Teaching and Research, 2018)
This research was done because most of student still encounter problems in mastering English especially vocabulary mastery. Most of the students were difficult to memorize the new word eventhough they have studied English before. Then, the atmosphere of the classroom was not conductive and the students tend to be sleepy and bored in the classroom. Based on these facts,  the researcher need to seek the problems and the solution of these. One of them is using card sort in vocabulary mastery. It belong to applying by using card sort activity. The instrument used in this research was multiple choice. The activity must be validated to the experts by using multiple choice sheet. After analyzing the data, it was found that the students’ vocabulary mastery by using card sort was better than the students who are not taught by using card sort activity. It means that by using card sort in teaching English gives significant effect toward students’ vocabulary mastery.Key words :Card Sort, Vocabulary, Effect, and Vocabulary Mastery